The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.3143/geriatrics.42.34
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of elderly pneumonia by pneumococcal, influenza and BCG vaccinations

Abstract: Pneumonia is a major cause of morbidity and mortality in elderly people, especially in those with chronic medical conditions such as chronic heart and lung diseases. We prospectively examined the effect of influenza and pneumococcal vaccinations on the rate of hospitalization for and complications of pneumonia, all respiratory tract conditions and mortality in elderly bedridden patients and found that both febrile days and pneumonia cases decreased. Thus, these results show that it is valuable to vaccinate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 0 publications
4
60
0
1
Order By: Relevance
“…Encouraging data also emerged from a recent double-blind, randomized clinical trial, showing that patients ≥ 65 years vaccinated with BCG had a reduced incidence of infections, in particular respiratory tract infections 9 . This study is in line with other previous reports showing a reduction in respiratory tract infections in the BCG vaccinated cohort 10 , 11 .…”
Section: Introductionsupporting
confidence: 94%
“…Encouraging data also emerged from a recent double-blind, randomized clinical trial, showing that patients ≥ 65 years vaccinated with BCG had a reduced incidence of infections, in particular respiratory tract infections 9 . This study is in line with other previous reports showing a reduction in respiratory tract infections in the BCG vaccinated cohort 10 , 11 .…”
Section: Introductionsupporting
confidence: 94%
“…A small study in Indonesia in the elderly reported that multiple doses of BCG vaccination resulted in a significant reduction in the number of respiratory tract infections compared with a placebo (Wardhana et al, 2011). A clinical trial in Japan found a reduced risk of pneumonia upon BCG vaccination in previously tuberculin-negative elderly people (Ohrui et al, 2005).…”
Section: Reprogramming Innate Immune Responses: Trained Immunity and mentioning
confidence: 99%
“…Importantly for the at-risk populations for severe COVID-19, it was shown that BCG had a similar protective effect on respiratory tract infections in older individuals in Indonesia (172). In addition, a clinical trial performed in older individuals in Japan established protection against pneumonia after pneumococcal, influenza and BCG vaccinations (173). Further confirmation of this effect has been demonstrated in a randomized controlled trial in which BCG vaccination protected against experimental infection of a yellow fever virus (174).…”
Section: Trained Immunity Utility For Vaccinesmentioning
confidence: 90%